(untitled) (Jurnal Teknologi Industri Pertanian, 2023)
Gayo Arabica coffee is a high-quality specialty coffee with a distinctive, complex aroma and a fairly strong viscosity. By developing a visualization of the Gayo Arabica coffee packaging design, the coffee product is expected to be more accepted in the market according to consumer preferences. This study aimed to formulate a strategy for developing visualization of the Gayo Arabica coffee packaging design. Factors that cover the problem of packaging design visualization included colour, shape, brand, illustration/image, information/labeling, and local and cultural wisdom. The formulation strategy for packaging design visualization development could be completed using the soft systems methodology (SSM). The use of the SSM method providds two recommended activities, namely technical activities and policy activities. The results of this study can be used as a reference or reference for the industry or interested parties in considering the visualization of designs related to the packaging of Gayo Arabica coffee products. Keywords: Aceh, conceptual model, Gayo arabica, rich picture, soft systems methodology